Analysis competitiveness and exchange rate effect on indonesian terms of trade 1995-2016 - Goestjahjanti, Francisca Sestri (Jurnal Manajemen, 2018)
The purpose of this research is to discuss and review the influence of competitiveness and exchange rates to Indonesian term of trade. The problem of this research is how the influence of competitiveness and exchange rate variable simultaneously and partially to Indonesian term of trade. This research used secondary data time series for 22 years since 1995 to 2016. The research method used explanatory research to explain the causal relationship between the variables in a model, through hypothesis testing. The analysis employed statistical technique of linear regression with the software SPSS -22 and E-views-7. The results of the researches showed that these variables competitiveness and exchange rate are simultaneously and partially give positive and significant effect on Indonesian term of trade.